Clinicoetiological profile and risk assessment of newborn with respiratory distress in a tertiary care centre in South India - Sahoo, Manas Ranjan; Vasundhara, Arigela; Rao, Majeti Srinivasa; Alekhya, Jampana; Nagasree, Pydi (International Journal of Contemporary Pediatrics, 2017)
Background: Respiratory distress is one of the common manifestation for which newborn seeks admission into NICU. As preterm care is increasing more use of surfactant, CPAP, mechanical ventilation has been seen in managing respiratory distress in newborn. This study has been undertaken to evaluate the various etiological factors, various maternal and neonatal risk factors associated with the development of severe respiratory distress, need for surfactant, CPAP and mechanical ventilation in newborns with respiratory distress and finally to assess the immediate clinical outcome of respiratory distress in newborns in our NICU. Methods: The present study was conducted in the department of Pediatrics at Alluri Sitarama Raju academy of medical sciences hospital, Eluru, between August 2012 and August 2014 (over a period of 24 months). It is a prospective study. Results: Out of 100 newborns admitted with respiratory distress, 90% were of respiratory origin. Most common cause was TTNB (32%) but severe distress was contributed maximum by HMD (44.82% of severe distress). Conclusions: Transient tachypnoea of newborn is the most common cause among newborns with respiratory distress. Majority of newborns develop severe distress immediately after birth. Newborns with gestational age between 28-30 weeks are more prone to develop severe respiratory distress. Newborns weighing <1.5 kg are more prone for development of severe distress. Newborns with one minute APGAR score of <7 are more prone to develop severe distress.